Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 8 - Section 8.2 - The Quadratic Formula - 8.2 Exercises: 23

Answer

$x=\left\{ \dfrac{-1-\sqrt{29}}{2},\dfrac{-1+\sqrt{29}}{2} \right\}$

Work Step by Step

$\bf{\text{Solution Outline:}}$ To find the solutions of the given equation, $ (x+2)(x-3)=1 ,$ express first in the form $ax^2+bx+c=0.$ Then use the Quadratic Formula. $\bf{\text{Solution Details:}}$ Using the FOIL Method which is given by $(a+b)(c+d)=ac+ad+bc+bd,$ the expression above is equivalent to\begin{array}{l}\require{cancel} x(x)+x(-3)+2(x)+2(-3)=1 \\\\ x^2-3x+2x-6=1 \\\\ x^2-x-6=1 .\end{array} Using the properties of equality, in the form $ax^2+bx+c=0,$ the expression above is equivalent to \begin{array}{l}\require{cancel} x^2-x-6-1=0 \\\\ x^2-x-7=0 .\end{array} The quadratic equation above has $a= 1 , b= -1 , c= -7 .$ Using $x=\dfrac{-b\pm\sqrt{b^2-4ac}}{2a}$ or the Quadratic Formula, then \begin{array}{l}\require{cancel} x=\dfrac{-1\pm\sqrt{1^2-4(1)(-7)}}{2(1)} \\\\ x=\dfrac{-1\pm\sqrt{1+28}}{2} \\\\ x=\dfrac{-1\pm\sqrt{29}}{2} .\end{array} The solutions are \begin{array}{l}\require{cancel} x=\dfrac{-1-\sqrt{29}}{2} \\\\\text{OR}\\\\ x=\dfrac{-1+\sqrt{29}}{2} .\end{array} Hence, $ x=\left\{ \dfrac{-1-\sqrt{29}}{2},\dfrac{-1+\sqrt{29}}{2} \right\} .$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.